2002
DOI: 10.1128/aem.68.6.2676-2682.2002
|View full text |Cite
|
Sign up to set email alerts
|

Isomaltulose Synthase from Klebsiella sp. Strain LX3: Gene Cloning and Characterization and Engineering of Thermostability

Abstract: The gene (palI) encoding isomaltulose synthase (PalI) from a soil bacterial isolate, Klebsiella sp. strain LX3, was cloned and characterized. PalI converts sucrose into isomaltulose, trehalulose, and trace amounts of glucose and fructose. Sequence domain analysis showed that PalI contains an ␣-amylase domain and (␤/␣) 8 -barrel structures, suggesting that it belongs to the ␣-amylase family. Sequence alignment indicated that the five amino acid residues of catalytic importance in ␣ Isomaltulose (6-O-␣-D-glucopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 37 publications
1
59
0
Order By: Relevance
“…Until now very little has been reported concerning the enhancement of thermoactivity, thermostability and catalytic efficiency of sucrose isomerases (Zhang et al 2002). For industrial applications it is of interest to operate with biocatalysts being thermoactive and thermostable.…”
Section: Biochemical Properties Of Sucrose Isomerasesmentioning
confidence: 99%
See 3 more Smart Citations
“…Until now very little has been reported concerning the enhancement of thermoactivity, thermostability and catalytic efficiency of sucrose isomerases (Zhang et al 2002). For industrial applications it is of interest to operate with biocatalysts being thermoactive and thermostable.…”
Section: Biochemical Properties Of Sucrose Isomerasesmentioning
confidence: 99%
“…Zhang et al (2003a) reported that the reaction end-products were clearly related to the charge of the catalytic pocket. Thus, operating at pHs higher than the enzymes optimal pH allow the formation of trehalulose, whereas at lower pH the production of glucose and fructose was promoted (Nagai et al 1994;Zhang et al 2002;Wu & Birch 2005). The kinetic parameters of various sucrose isomerases are presented in Table 1.…”
Section: Biochemical Properties Of Sucrose Isomerasesmentioning
confidence: 99%
See 2 more Smart Citations
“…rhapontici, 12,15) Klebsiella sp. LX3, 40) Klebsiella sp., 41) K. planticola CCRC 19112, 42) Pantoea dispersa, 43) and Enterobacter sp. FMB1, 11) which produce mainly isomaltulose (75 85%), and A. radiobacter MX 332 37) and Ps.…”
Section: )mentioning
confidence: 99%